Effectiveness of Poetry Therapy on the clients of Post-Traumatic Stress Disorder - Naz, Iqra; Khan, Shumaila Mukhtar; Shahzadi, Iqra; Nazar, Amina Naz; Mahnoor (Pakistan Journal of Humanities and Social Sciences, 2024)
The purpose of the study is to explore the effectiveness of Poetry Therapy for the clients of Post-Traumatic Stress Disorder. Quasi experimental design (pre and post design) along with purposive sampling technique was employed on the sample size of 05 participants (females) to find the effectiveness of therapy. Participant was selected only from Punjab province. Therapy was applied in one to one session. There was four therapeutic sessions applied for the management of PTSD. Each session was last for 45- 1 hour approximately. It was a 1-week program alternative days (Monday, Wednesday, Friday). PTSD Scale-Self Report for DSM-5 was employed to access the client's symptoms of post-traumatic stress. Statistical package SPSS 26 was used to figure-out the outcome of the research. Reliability analysis, Wilcoxon signed ranked analysis was used to check the effectiveness of poetry therapy. The findings showed that the reliability of PTSD scale has demonstrated a moderate level of reliability (? = .87). Additionally, the poetry therapy was found to be significantly effective in managing post-traumatic stress. The results showed a clear and significant difference between pre-assessment and post-assessment scores on the PTSD scale. In conclusion, Poetry Therapy, which utilizes poems, stories, and other spoken or written materials, is a form of expressive arts therapy that aids in emotional healing and well-being. Understanding the effectiveness of poetry therapy enhances our ability to manage various disorders and promotes mental health in a highly effective manner.